Acute high frequency stimulation of the prefrontal cortex or nucleus accumbens does not increase hippocampal neurogenesis in rats. (September 2015) - Winter, Christine; Bregman, Tatiana; Voget, Mareike; Raymond, Roger; Hadar, Ravit; Nobrega, José N.; Hamani, Clement
Abstract: To date, the effects of deep brain stimulation (DBS) on hippocampal neurogenesis have been mainly characterized in the context of memory. Acute stimulation (i.e. for 1 h) of either the entorhinal cortex or the anterior thalamus increases both cell proliferation and survival. We investigate whether stimulation applied to targets being considered for the treatment of depression, namely the ventromedial prefrontal cortex (vmPFC) or nucleus accumbens (Acb), also increases hippocampal neurogenesis in rodents. Rats were treated with vmPFC or Acb DBS for 1 h at different settings. 5′-bromo-2′deoxyuridine (BrdU) was injected three days following stimulation onset and animals were sacrificed 24 h or 28 days later. Overall, we found that neither vmPFC nor Acb DBS increased hippocampal neurogenesis. In summary, the delivery of acute stimulation into targets homologous to those used in human depression trials does not increase hippocampal neurogenesis.